Electrostimulation as a conservative treatment for urinary incontinence in women - Terlikowski, Robert; Dobrzycka, Bożena; Piechocka, Dorota I.; Kulesza-Brończyk, Bożena; Lejmanowicz, Krzysztof; Terlikowski, Sławomir J.; Kinalski, Maciej (Polish Journal of Public Health, 2009)
Introduction. Due to the increasing population of women in senium, urinary incontinence (UI) has become a more and more significant problem. UI is not a chronic illness but a symptom that occurs in the clinical syndrome of various aetiology. Therefore, it requires a diverse diagnostic and therapeutic management.  Aim of the study. The aim of the current study was to evaluate the effectiveness of a six-week conservative treatment of urinary stress incontinence (USI) using the transvaginal electrical stimulation (TVES) method.  Material and methods. The therapeutic group consisted of women who underwent the urogynecological examination. The aim of this examination was an objective evaluation of the severity and type of UI. All the patients completed the Gaudenz questionnaire and the Polish version of I-QoL survey before and after the therapy. Treatment took place on an outpatient basis, with the use of a NeuroTracTM device produced by Verity Medical Ltd. (UK). A vaginal electrode was applied according to the producer’s instructions and then the intensity of stimulation that caused an evident spasm and was accepted by the patient was determined. The parameters of muscle stimulation were selected individually: the frequency range from 10 to 40 Hz, impulse width from 200 to 250 μs, run time/decontraction in configuration of 15 s/30s, for 20 minutes. The treatment lasted for 6 weeks, twice a week on average. Conclusions. TVES contributes significantly to the decrease in voiding frequency, nocturia, daily uncontrolled urine leak and leads to a reduced use of sanitary protection. TVES improves life quality in USI patients, has a psycho-sociological effect and reduces social embarrassment.